Meningkatkan Kemampuan Melewati Jalan Sempit dengan Menggunakan Teknik Pendamping Awas pada Anak Tunanetra di SLB-A Bartemeus Manado - Salma Gaghenggang (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to describe the effectiveness of the alert companion technique for the skills of passing narrow roads in blind students. This study used a single subject design method. Based on the facts found by researchers in the field, children with visual impairment in using the watchful companion technique to pass through narrow roads still require very large attention from people / mentors. The daily activities of blind children cannot be separated from their walking activities. Therefore, it requires special attention to be able to do activities properly. To support the activities of blind children, a watchful companion is needed to make it easier to carry out activities. The watchful companion technique for passing narrow roads is a method or technique to help blind children carry out their daily activities.